Anticancer activity of heptazoline against the SCC-15 human oral cancer cells and inhibition of PI3K/AKT signalling pathway. Issue 1 (31st December 2022) - Zhang, Hongmei; Xun, Wenxing; Guo, Shaoxiong; Wang, Xiaoxia; Liu, Xiaolu
Abstract : Current research endeavours are focusing to develop potent chemotherapy for oral cancer. Consistently, this study examined the anticancer effects of heptazoline on the human oral cancer cells. The findings of the present study revealed that heptazoline suppressed the growth of all the oral cancer SCC-15 oral cancer cells (IC50 ; 12 µM) with very low cytotoxic effects on the normal hTRET-OME cells (IC50 ; 85 µM). The comet and DAPI assay showed DNA damage as well other signs of apoptosis induced by heptazoline in SCC-15 cells. Annexin V/PI assay revealed that apoptotic SCC-15 cells increased from 3.5% at 0 µM to 21.27% at 24 µM of heptazoline Additionally, the expression of Bax was upregulated and that of Bcl-2 was downregulated upon heptazoline treatment of the SCC-15 cells. Heptazoline also increased the expression of caspase-3 further confirming the induction of apoptosis. Investigation of the effects of heptazoline on the PI3K/AKT signalling showed a remarkable decrease in the phosphorylation of PI3K and AKT. Taken together, the findings of the study suggest that heptazoline has potent anticancer activity and may serve as a lead molecule in oral cancer treatment.